Progress in Artificial Intelligence 15th Portuguese Conference on Artificial Intelligence, EPIA 2011, Lisbon, Portugal, October 10-13, 2011. Proceedings - Antunes, Luis.; Pinto, H. Sofia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book contains a selection of higher quality and reviewed papers of the 15th Portuguese Conference on Artificial Intelligence, EPIA 2011, held in Lisbon, Portugal, in October 2011. The 50 revised full papers presented were carefully reviewed and selected from a total of 203 submissions. The papers are organized in topical sections on affective computing, ambient intelligence environments, artificial intelligence methodologies for games, artificial intelligence in transportation systems, artificial life evolutionary algorithms, computational logic with applications, general artificial intelligence, intelligent robotics, knowledge discovery and business intelligence, multi-agent systems: theory and applications, social simulation and modeling, text mining and applications, and doctoral symposium on artificial intelligence.
Keywords: Computer science; Database management; Data mining; Artificial intelligence; Computer simulation; Computer vision; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Simulation and Modeling; Computer Imaging, Vision, Pattern Recognition and Graphics; Data Mining and Knowledge Discovery; Database Management